KESANTUNAN BERBAHASA DALAMNOVEL 99 CAHAYA DI LANGIT EROPAKARYA HANUM SALSABIELA RAISDANRANGGA ALMAHHENDRA - Priscilia, Yola Maulina; ', Charlina; Rahman, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRAC: This research discusses about the politeness of indonesian’s language in a Novel 99 Cahaya di Langit Eropa by Hanum Salsabiela Rais and Rangga Almahendra. The aim of this research is to identify and analyze the politenes of indonesian’s language in Novel 99 Cahaya di Langit Eropa by Hanum Salsabiela Rais and Rangga Almahendra. To determine the politeness of Indonesian’s Language used scale of the Language. Writer used Theory by Brown and Levinson for determine scale of Politeness of Indonesian’s Language. Politenes The main source of this research is the Novel 99 Cahaya di Langit Eropa by Hanum Salsabiela Rais and Rangga Almahendra. The method that used in the research is descriptive analitic whit the techniques of the data collection obtained from the documentation of the data. The politeness of Indonesian’s language that studied in this novel contains the principle of good manners by Leech theory that consist of six maxim. There are (1) tact maxim, (2) Generosity maxim (3) Aprobation maxim, (4) Modesty maxim (5) Agreement maxim, and the last is Symphaty maxim.Key Words: Politeness of language, maxim, novels 99Cahaya di Langit Eropa